EFISIENSI TEKNIS USAHATANI PADI SAWAH PADA PERTANIAN PERKOTAAN DI KOTA SEMARANG: PENDEKATAN STHOCHASTIC FRONTIER - Nur Muttaqien Zuhri; Ali Khamdi; Nun Maulida Suci Ayomi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Improving food self-sufficiency requires a strategy to increase paddy rice production. The urban agriculture initiative in Semarang City is seen as a suitable policy. However, the current increase in agricultural productivity through improved production efficiency is hampered by land conversion and inappropriate use of production inputs. The objective of this study is to assess the technical efficiency of wet-rice farming and its influencing factors in Semarang City. Cross-sectional data from 68 respondents were used in this study. The data analysis strategy used in this study is Maximum Likelihood Estimation (MLE) combined with Stochastic Frontier Cobb Douglas production function. The results show that land area, seeds, NPK, urea, and pesticides are the main determinants of rice production. Paddy rice cultivation in Semarang City is technically efficient (0.73). Formal education and other sources of off-farm income are factors that influence the level of technical inefficiency of wet-rice cultivation. Strategies to achieve food self-sufficiency in urban agriculture include developing extension strategies and improving agricultural infrastructure.